Effectiveness of an oral health training program for school teachers in India: An interventional study - Charu Khurana; Harsh Priya; O P Kharbanda; Upendra S Bhadauria; Diptajit Das; Priyanka Ravi; D S Monica Dev (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: Schools are a valuable platform for promoting oral health through oral health education as the children spend most of their active time in schools. Training school teachers on oral health promotion will help to inculcate healthy oral habits in children during their formative years of life. OBJECTIVES: The objective of this study was to assess the knowledge, attitude, approach, and action change of school teachers toward oral health and the impact of this training intervention in improving their knowledge. MATERIALS AND METHODS: An interventional study was conducted among 50 primary school teachers across the country selected by the Ministry of Human Resource Development. A self-administered, 28-item questionnaire in Google document format was developed to evaluate the knowledge and practice of teachers toward oral hygiene before and after the teachers' training program. The training was done using a validated training manual on oral health promotion for school teachers developed by the Ministry of Health and Family Welfare. Needs assessment for training was conducted 1 week before this training program. STATISTICAL ANALYSIS: Wilcoxon signed-rank test and Mc Nemar tests were used to assess the difference between the scores before and after oral health education. RESULTS: The needs assessment revealed that majority of the teachers felt the need to participate in oral health promotion training. A significant increase (P < 0.001) in mean knowledge scores of school teachers was seen after a 1-day training program. CONCLUSION: The training improved the knowledge of school teachers on oral health which indicates that the adopted method of oral health education was well received by the participants from all over the country.